Inovasi Administratif: Fungsi Dan Metode Organisasi PT PWD Insurance Bandung - Ajat Sudrajat; Yayan Sofyan; Siti Rosmayati (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the magnitude of the effect of organizational functions and methods on administrative innovation. This study adopted a quantitative method, adopted a non-experimental and horizontal design. Through transaction research on the sample of PT PWD Insurance Bandung. Sampling of PT PWD Insurance Bandung is for convenience. The results of this research on organizational functions and methods are predictive of administrative innovation. As long as PT PWD Insurance Bandung encourages the development of training and knowledge methods, development of independent methods for employees, and when PT PWD Insurance Bandung conducts performance evaluations, the new method will be able to formulate and standardize management procedures and procedures, distribution of responsibilities and benefits among employees, and to develop new structural concepts for the workplace, organizational practices, and external relations.